The German Basic Income System in the European Context - Regina Konle-Seidl (Wirtschaftsdienst)
Abstract While the European Commission envisages a strengthening of minimum income schemes as part of the implementation of the European Pillar of Social Rights, the political debate in Germany is characterised by proposals of varying scope for reforming the basic income system for jobseekers (“Hartz IV”). This article places the German basic income system in the European context and discusses its role and performance from a European perspective. Against this background, the article also discusses proposals for reforming the “Harz IV system”.